Religion uden Religion: En nærlæsning af Jacques Derridas Tro og Viden – De to kilder til “religionen” ved den blotte fornufts grænser - Damgaard, Gustav G. (Dansk Teologisk Tidsskrift, 2025)
This article develops the notion of religion in Jacques Derrida’s central work Faith and Knowledge. Focusing especially on the question of abstraction and doubling, the article suggests the structure of a “religion without religion” as the implicit theme of Derrida’s text. With Derrida, the article argues that the structure of a “religion without religion” would give rise to the possibility of a notion of religion and faith beyond the limits of classical onto-theology. Drawing on related texts from Derrida’s authorship concerning the question of religion such as Archive Fever and The Gift of Death, the article proposes the notion of a messianic promise in the form of an original affirmation as the quasi-transcendental condition of Derrida’s notion of religion.